Hernandezine induces autophagic cell death in hepatocellular carcinoma cells via the AMPK/mTOR signaling pathway - WANG Jun, HU Gangfeng, GAO Weichen, WANG Lubing (Waike lilun yu shijian, 2025)
Objective To investigate the autophagy activation effect of hernandezine (HER) on hepatocellular carcinoma (HCC) cells and its role in inducing autophagic cell death. Methods The inhibitory effects of HER on the proliferation of HCC cell lines Hep 3B and Huh-7 were assessed using CCK-8 assay. HCC cells were treated with HER at different concentrations and time points gradient. Western blot analysis was performed to evaluate the conversion of autophagy marker LC3 from type Ⅰ to type Ⅱ and the levels of SQSTM1/p62. Stable red fluorescent protein(RFP)-LC3-expressing cell lines were established through lentiviral infection, and the accumulation of RFP-LC3 puncta following HER treatment was observed under confocal microscope. Autophagosomes in HER-treated cells were visualized using transmission electron microscopy. The effects of autophagy inhibitors, bafilomycin A1 (BafA1) or hydroxychloroquine (HCQ), in combination with HER were investigated by analyzing cell death rates via flow cytometry. The phosphorylation levels of adenosine 5′-monophosphate(AMP)-activated protein kinase(AMPK) and mammalian target of rapamycin(mTOR) were assessed by Western blot.Results HER inhibited the proliferation of HCC cells Hep 3B and Huh-7, promoted the conversion of LC3-Ⅰ to LC3-Ⅱ, and activated autophagy in a dose- and time-dependent manner. Confocal microscopy and transmission electron microscopy revealed a significant increase in autophagic vesicles in HER-treated cells. HER-induced cell death was attenuated by the autophagy inhibitors BafA1 or HCQ. HER treatment increased AMPK phosphorylation levels while decreasing mTOR phosphorylation levels.Conclusions HER induces autophagy and promotes autophagic cell death in HCC cells via the AMPK/mTOR signaling pathway.